2014
DOI: 10.1111/jfr3.12105
|View full text |Cite
|
Sign up to set email alerts
|

Continuous, large‐scale simulation model for flood risk assessments: proof‐of‐concept

Abstract: In this paper we present the Regional Flood Model (RFM), a process‐based model cascade developed for large‐scale basins. The objective of this study is to demonstrate that flood risk assessments, based on a continuous simulation approach, including rainfall–runoff, 1D river network, 2D hinterland inundation and damage estimation models, are feasible at the scale of large catchments. RFM is applied to the German part of the Elbe catchment including around 2700 river‐km. For this proof‐of‐concept study, simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 55 publications
1
105
0
Order By: Relevance
“…The spatial detail of the simulated inundation depths depends on the discretization level of the model setup which is usually below 100 m horizontal resolution (Horritt and Bates, 2002;Falter et al, 2014). The near-real-time application of hydrodynamic-numeric models is hampered by the need to provide appropriate estimates of initial and boundary conditions, to assimilate model simulations and observations (Matgen et al, 2007) and by considerable computational costs .…”
Section: State Of the Art And Related Workmentioning
confidence: 99%
“…The spatial detail of the simulated inundation depths depends on the discretization level of the model setup which is usually below 100 m horizontal resolution (Horritt and Bates, 2002;Falter et al, 2014). The near-real-time application of hydrodynamic-numeric models is hampered by the need to provide appropriate estimates of initial and boundary conditions, to assimilate model simulations and observations (Matgen et al, 2007) and by considerable computational costs .…”
Section: State Of the Art And Related Workmentioning
confidence: 99%
“…Most of these studies identified the outputs from GHMs and GRMs as major sources of uncertainty. Falter et al (2016) specifically pointed to the uncertainties coming from discharge simulations and 1-D hydrodynamic simulations in river channels. Winsemius et al (2013) pointed out that more focus should be placed on studying the behavior of the GHMs and GRMs during extremes.…”
Section: Introductionmentioning
confidence: 99%
“…The modeling framework was implemented and validated in Bangladesh. A model cascade consisting of a regional rainfall-runoff model, a 1-D diffusive wave river routing model, and 2-D raster-based flood inundation model was used by Falter et al (2016) to simulate flood risks at the Elbe River. Dottori et al (2016) used the discharge outputs (available at 0.1 • resolution) from the model cascade of GloFAS (Alfieri et al, 2013) to calculate the discharge maxima at several return periods.…”
Section: Introductionmentioning
confidence: 99%
“…As flood events in most cases are heterogeneous in space and time [4,5], the use of homogenous flood scenarios may lead to inaccurate results [6,7]. Therefore, heterogeneous flood scenarios, which take into account the spatial variability of flood events, should be considered in flood risk analysis [6,8,9].…”
Section: Introductionmentioning
confidence: 99%